j(j-8)=0

Simple and best practice solution for j(j-8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for j(j-8)=0 equation:


Simplifying
j(j + -8) = 0

Reorder the terms:
j(-8 + j) = 0
(-8 * j + j * j) = 0
(-8j + j2) = 0

Solving
-8j + j2 = 0

Solving for variable 'j'.

Factor out the Greatest Common Factor (GCF), 'j'.
j(-8 + j) = 0

Subproblem 1

Set the factor 'j' equal to zero and attempt to solve: Simplifying j = 0 Solving j = 0 Move all terms containing j to the left, all other terms to the right. Simplifying j = 0

Subproblem 2

Set the factor '(-8 + j)' equal to zero and attempt to solve: Simplifying -8 + j = 0 Solving -8 + j = 0 Move all terms containing j to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + j = 0 + 8 Combine like terms: -8 + 8 = 0 0 + j = 0 + 8 j = 0 + 8 Combine like terms: 0 + 8 = 8 j = 8 Simplifying j = 8

Solution

j = {0, 8}

See similar equations:

| 25/31.25= | | -9m=18 | | 4m(m-8)=0 | | 6=-4y+18 | | b^5+10b^4=0 | | 1/4x-2/5=5/6 | | (w-8)(3w+7)=0 | | 4-(2x+3)=5x-8 | | 1=v-8 | | -5-4r=-(1-2r) | | -9=2+p | | 8x-(5-x)+2(3x-4)=2 | | 3x^2=-18 | | 3r-4=5(r-1) | | 3k=45 | | 2(7/2)+y=11 | | 3(x-2)=-31+4x | | 8m+m-m-3m+2m=14 | | 3(2x+5)-5= | | 19s-13s-6s+s=19 | | 8.8=m-14.4 | | 7x+2y=94 | | 152+8x=-82-10x | | v^2-5vy-14y^2=0 | | 5r-1=-3(-4+3r)+r | | 2y=7x-94 | | (2s-9)(8s+1)=0 | | 19s-13s-6s=19 | | 3c+2=6c | | 5(m+9)=40+2m+5+3m | | 10x^2=60x+2 | | 4+2(x-8)=8-4x+2 |

Equations solver categories